2016
DOI: 10.1089/ten.tea.2015.0524
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factor-Mediated Migration of Bone Marrow Progenitor Cells for Accelerated Scaffold Recruitment

Abstract: Tissue engineering approaches using growth factor-functionalized acellular scaffolds to support and guide repair driven by endogenous cells are thought to require a careful balance between cell recruitment and growth factor release kinetics. The objective of this study was to identify a growth factor combination that accelerates progenitor cell migration into self-assembling peptide hydrogels in the context of cartilage defect repair. A novel 3D gel-to-gel migration assay enabled quantification of the chemotac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 92 publications
(124 reference statements)
1
22
0
1
Order By: Relevance
“…Similarly, in an in vitro rabbit model this combination also showed superior chemotactic effects on MSCs compared with either growth factors alone . The authors believe this is the first example of an in vivo application of these growth factors in a cartilage repair model, which supports our in vitro work …”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Similarly, in an in vitro rabbit model this combination also showed superior chemotactic effects on MSCs compared with either growth factors alone . The authors believe this is the first example of an in vivo application of these growth factors in a cartilage repair model, which supports our in vitro work …”
Section: Discussionsupporting
confidence: 82%
“…Our group has reported that HB‐IGF‐1 is strongly retained in articular cartilage post‐intra‐articular injection and leads to sustained proteoglycan biosynthesis in cartilage explants . Interestingly, an in vitro kinetics study showed that 84% of the HB‐IGF‐1 that was premixed into a KLD hydrogel was released within the first four days of culture; however, this HB‐IGF‐1 seems to be bound by surrounding cartilage annuli instead of being released in the media. Further studies are necessary to elucidate the lack of effect in the present study.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations